Konstruksi Tematik Ayat-Ayat Hukum (Konsep dan Dasar Seleksi Ayat Hukum Menurut Al-Tahawi) - Siregar, Ahmad Sholihin; Nuruddin, Amiur; Qorib, Ahmad (Fakultas Syariah IAIN Purwokerto, 2017)
This research begins from the unavailability of basis in selecting legal verses. Therefore, this research aims to construct the foundation of selecting legal verses starting from the selection done by al-Tahawi. This research is normative law research (doctrinaire, dogmatic). The research object is legal verses of al-Tahawiâ€™s selection found in Aá¸¥kÄm al-Qurâ€™Än. The object is approached by using mimetic and objective approach. There are two foundations used by al-Tahawi in selecting legal verses; textually and contextually. The textual foundation consists of the availability or unavailability of mukallaf action in a verse. The contextual foundation consists of asbÄb al-nuzÅ«l and explaining hadis. From the selection basis, the characteristic of legal verses is also constructed textually and contextually. The textual characteristic consists of keywords showing law content such as: lÄ junÄá¸¥a, laisa á¸¥araj, á¸¥urrima, uá¸¥illa, kutiba, farÄ«á¸ah, al-á¹£alÄt, al-á¹£aum, al-zakÄh, al-á¸¥ajj, ar-rafaá¹¡. Contextual characteristic consists of: asbÄb al-nuzÅ«l of a legal verse should be related to a legal matter, and there are explaining hadis showing the existence of law content in certain verses.